SYNTHESIS AND CHARACTERIZATION OF HPMC/HAp/Fe3O4 COMPOSITE FOR HYPERTHERMIA APPLICATION - Muflikhah Muflikhah; Wildan Zakiah Lubis; Irma Septi Ardiani; Khoirotun Nadiyyah; Sulistioso Giat Sukaryo (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
SYNTHESIS AND CHARACTERIZATION OF HPMC/HAp/Fe3O4 COMPOSITE FOR HYPERTHERMIA APPLICATION. Magnetic material become subject of intense research for hyperthermia application, and injectable magnetic hyperthermia for bone cancer is one of this research interest. In this study, composite of hydroxyapatite (HAp) and Fe3O4 in Hydroxypropyl-methyl cellulose (HPMC) matrix (HPMC/HAp/Fe3O4) has been synthesized in gel form that are expected can be applied for injectable bone substitute (IBS) in hyperthermia therapy. Composites were made using conventional methods by mixing HAp powder with ferrofluid Fe3O4 in HPMC solution. The composition of the composites were varied with the mass comparison of HPMC: HAp: Fe3O4 was 1: 0: 0; 1: 3: 0; 1: 2: 0.5; 1: 1: 0.25; and 1: 0: 3. The physical, chemical, and magnetic properties of the composites were characterized using X-Ray Diffractometer (XRD), Fourier Transform Infrared Spectrometry (FT-IR), Particle Size Analyzer (PSA), and Vibrating Sample Magnetometer (VSM). The XRD characterization results of the HPMC/HAp/Fe3O4 composite showed the crystalline phase of the constituent components. Saturation magnetization of the HPMC/HAp/Fe3O4 composite was 2.72 emu/g and 1.79 emu/g for the composition of 1: 2: 0.5 and 1:1:0.25 respectively. HPMC/HAp/Fe3O4 composite has superparamagnetic and biocompatible properties, so that can be applied as IBS in hyperthermia therapy for bone cancer.